South-South Cooperation or Core-Periphery Contention? Ghanaian and Zambian Perceptions of Economic Relations with China. Issue 3 (3rd May 2021) - Flint, Colin; Waddoups, Madeleine
ABSTRACT: The geopolitics of development are explored through an examination of development assistance to two African countries as a mechanism of competition between China and the US. The processes of competition include the actions and rhetoric of African leaders. We define a geopolitical context for the agency of political leaders and opinion-makers in Ghana and Zambia. The geopolitical context consists of the structure and dynamics of the world-economy; especially the competition to capture the newest round of innovations and the related need to establish supply chains of raw materials from peripheral countries. By analysing quotes from Ghanaian and Zambian elites we identify the possibility for geopolitical agency in the periphery that is constrained by, and largely maintains, China-US competition and the core-periphery hierarchy of the world-economy.